2015
DOI: 10.4236/fns.2015.610095
|View full text |Cite
|
Sign up to set email alerts
|

The Physicochemical Changes of Farm-Raised Pacific White Shrimp (<i>Litopenaeus vannamei</i>) as Influenced by Iced Storage

Abstract: Farm-raised Pacific white shrimp (Litopenaeus vannamei) freshly harvested was evaluated for differences in proximal composition (moisture, ash, fat, and protein contents), water activity (aw), water retention index (WRI), pH, colour and texture of up to 12 days of iced storage. Shortly after harvest, the proximate composition of shrimp appeared comparable across the farms. With ice storage, the pH significantly increased whereas fat content slowly decreased particularly between days 3 and 9 (P < 0.05), after w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 49 publications
(79 reference statements)
2
32
0
1
Order By: Relevance
“…Due to an abundance of polyphenol oxidase in shrimp, it reacted effortlessly with DOPA substances to produce melanin (Bartolo & Birk, 1998). The observation seemed to agree with the color data reported by Okpala (2015) regarding the pink shrimp (Parapenaeus longirostris) that were processed onboard the shrimp under iced storage conditions. The observation seemed to agree with the color data reported by Okpala (2015) regarding the pink shrimp (Parapenaeus longirostris) that were processed onboard the shrimp under iced storage conditions.…”
Section: Changes In Colorsupporting
confidence: 86%
“…Due to an abundance of polyphenol oxidase in shrimp, it reacted effortlessly with DOPA substances to produce melanin (Bartolo & Birk, 1998). The observation seemed to agree with the color data reported by Okpala (2015) regarding the pink shrimp (Parapenaeus longirostris) that were processed onboard the shrimp under iced storage conditions. The observation seemed to agree with the color data reported by Okpala (2015) regarding the pink shrimp (Parapenaeus longirostris) that were processed onboard the shrimp under iced storage conditions.…”
Section: Changes In Colorsupporting
confidence: 86%
“…The increase in pH reflected the production of alkaline bacterial metabolites in spoiling shrimp muscle . The pH of the fresh L. vannamei ranged from 7.20 to 7.33 and the shrimps were of good quality before the pH reached 7.7 . The pH of L. vannamei increased to 7.6 at the seventh day of storage under 4 °C, 7.48 at the ninth day during chilled storage, and 7.6 at the eighth day of storage at −0.8 °C .…”
Section: Physicochemical Analysismentioning
confidence: 99%
“…The increase in the moisture content during ice storage may have been due to absorption from the melting ice. Annamalai et al () and Okpala () also reported some increase in the moisture content in L. vannamei during ice storage. In the current study, however, moisture content did not show any significant difference between the treatments.…”
Section: Resultsmentioning
confidence: 88%
“…Water holding capacity of the shrimp of this study in all the treatments decreased with storage time (Table ). This decrease in WHC indicates the denaturation/degradation of the protein during the storage (Okpala, ). The initial higher value (96.61%) of water holding capacity was observed in T 1 and lowest initial value (96.19%) was found in T 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation